Dealing with Privatization towards Internal Marketing Perspective - Sawagvudcharee, Ousanee (Business Administration and Management Journal Review, 2013)
The aim of this research is to understand the applicability of the concept of internal marketing (IM) for managing the particularities of a privatization process within a Thai state-owned enterprise (SOE), Provincial Electricity Authority (PEA). To address the research objective the following question was posed. In what forms the concept of internal marketing (IM) be applied towards a Thai SOE to create a positive attitude to transformational change during the privatization of the organization? This study was based on a subjective ontology and interpretivist epistemology. This research applied the case study approach to the PEA. A qualitative method for data collection was used. Semistructured interviews were conducted with people from four different levels of the organization’s hierarchy, these are from the operational, management, senior management, and top management level. The results showed that during the PEA’s privatization there were informed sources and factors that positively affected the process and lacks of techniques applied in the process, for instance, in information, communication, and coordination. Moreover, the process of privatization here showed less evidence of a professionally applied concept of IM. Therefore, the results from this research can be seen as a kind of a guideline for the implementation of IM to motivate the employees in the organization to get a better understanding of their contribution to the achievement of the organizational goals